2007
DOI: 10.1007/s11255-006-9137-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in elderly patients with acute renal failure in a developing country

Abstract: This prospective study was undertaken to systematically analyze the predictors of mortality in the elderly in a developing country. All elderly patients with ARF hospitalized at this tertiary care centre over 1 year were studied. Various predictors analyzed were hospital-acquired ARF, causative factors of ARF, preexisting hypertension and diabetes mellitus, severity of renal failure (initial and peak serum creatinine, need for dialysis), and complications of ARF: infection during the course of illness; serum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
8
1
Order By: Relevance
“…However, morbidity and mortality have not improved significantly [31][32][33]. Serum creatinine is an insensitive and late marker [34] for AKI.…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…However, morbidity and mortality have not improved significantly [31][32][33]. Serum creatinine is an insensitive and late marker [34] for AKI.…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…However, the average age of CA-AKI patients was younger, and the age gap between the survivor group and nonsurvivor group of CA-AKI was larger. These findings suggested that older patients with CA-AKI or HA-AKI were more susceptible to death and that age might be an important determinant of long-term outcome [1,[17][18][19].…”
Section: Introductionmentioning
confidence: 93%
“…Several risk models exist for predicting the prognosis in critically ill patients with AKI, especially in situations where AKI occurs as part of a multiple system organ failure. Until a validated method of assessing prognosis and predicting the outcome in the individual patient with AKI is available, most studies continue to show only general associations between reduced survival and various risk factors (including older age, greater burden of co-morbidity, chronic liver disease, higher severity of illness, severe sepsis/ septic shock, and post-cardiac surgical AKI) [74][75][76][77][78][79]. Recent data suggest that in critically ill patients with severe AKI, an RRT requirement independently predicted death [80].…”
Section: Prognosis Of Aki In Elderly Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies have attempted to explore the epidemiology of AKI in India. [15][16][17][18][19][20] However, these studies have either evaluated specific patient population or included patients outside the ICU, pediatric patients or have not used RIFLE or AKIN criteria to define, stratify or prognosticate AKI. Hence, in this study we aim to explore the epidemiology of AKI using both the RIFLE and AKIN criteria and to determine the prognostic validity of these criteria in an Indian ICU.…”
Section: Introductionmentioning
confidence: 99%